Cardiac involvement in lymphomas. Review of literature and case report of the clinical course of B-large-cell lymphoma - I. Yu. Gadaev; V. I. Ershov; O. V. Bochkarnikova; I. Ya. Sokolova; D. A. Budanova; E. S. Kotova; A. S. Lishuta (Столичная издательская компания, 2015)
Clinical case of successful chemotherapy of patient with cardiac involvement in lymphoma, one of manifestations of which was the heart rhythm and conduction disorder, is presented as illustration. The data on the epidemiology of cardiac involvement in hematologic diseases, particularly in lymphomas and their clinical manifestations, modern diagnostic and treatment are presented. Clinical case of successful chemotherapy of patient with cardiac involvement in lymphoma, one of manifestations of which was the heart rhythm and conduction disorder, is presented as illustration.